2010
DOI: 10.2463/mrms.9.227
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Plasmacytoma of the Sternum Detected Incidentally by MR Imaging of the Cervical Spine

Abstract: We incidentally detected a case of solitary plasmacytoma of the sternum by magnetic resonance (MR) imaging of the cervical spine. At detection, the patient had no symptoms, the lesion was localized in the bone marrow of the sternum, and there were noˆndings of bone destruction. The lesion showed high contrast on diŠusion-weighted images, gradually enlarged over 3 years, and was conˆrmed as a solitary plasmacytoma at open biopsy 3 years after detection. Radiologists should pay attention to incidentalˆndings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There are a few reports about EMP in the literature but we found only two literature concerning MRI features of nasal EMP. Besides we did not find any case of DWI concerning EMP but however, we came across with one case of plasmacytoma of the sternum that DWI was performed (Nakanishi et al, 2010). The MRI study reveals low to intermediate signal intensity on T1-and moderate to marked increased signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 97%
“…There are a few reports about EMP in the literature but we found only two literature concerning MRI features of nasal EMP. Besides we did not find any case of DWI concerning EMP but however, we came across with one case of plasmacytoma of the sternum that DWI was performed (Nakanishi et al, 2010). The MRI study reveals low to intermediate signal intensity on T1-and moderate to marked increased signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 97%
“…The majority of neoplasms of the sternum are metastases. Primary sternal neoplasms are uncommon and are much more frequently malignant than benign ( 2 ). In a study of the Chinese literature that reported 30 cases and reviewed a total of 248 cases of sternal tumors, the most malignant tumors were metastases, followed by myelomas, chondrosarcomas, lymphomas and osteosarcomas; the most benign tumors were chondromas and osteochondromas ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sternal plasmacytoma usually presents as an osteolytic expansile lesion or a typical ‘punched-out’ lytic lesion on radiological examination ( 15 ). The tumor usually destroys the cortex in several places and invades the soft tissues ( 2 , 4 ). CT may demonstrate a subtle lytic lesion or small soft-tissue masses of the sternal lesion that are not visible by radiography ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations